2009
DOI: 10.1111/j.1530-0277.2009.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adaptive Behavior in Children With Heavy Prenatal Alcohol Exposure or Attention‐Deficit/Hyperactivity Disorder

Abstract: Background Adaptive behavior, the ability to respond successfully to everyday demands, may be especially sensitive to the effects of heavy prenatal alcohol exposure. Similar adaptive dysfunction is common in other developmental disorders including attention-deficit/hyperactivity disorder (ADHD). ADHD is frequently present in alcohol-exposed children and this overlap in clinical presentation makes identification of alcohol-exposed children difficult. Direct comparison of children with prenatal alcohol exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
90
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 44 publications
14
90
0
Order By: Relevance
“…A literature review [100] comparing children with PAE and those with ADHD concluded that children with PAE had greater impairments in problem-solving, overall IQ, shifting attention, verbal fluency, verbal encoding, daily living skills, and face and emotion processing than do children with ADHD. Adaptive behavior deficits observed in children with PAE grow increasingly more severe with age, suggesting a progressive decline in functioning over time relative to children with ADHD [65]. Children with PAE were also found to have more difficulties with conditions associated with over-arousal, whereas children with ADHD and no history of PAE demonstrated deficits in conditions of underarousal [101].…”
Section: Child Psychiatry Hum Devmentioning
confidence: 96%
See 1 more Smart Citation
“…A literature review [100] comparing children with PAE and those with ADHD concluded that children with PAE had greater impairments in problem-solving, overall IQ, shifting attention, verbal fluency, verbal encoding, daily living skills, and face and emotion processing than do children with ADHD. Adaptive behavior deficits observed in children with PAE grow increasingly more severe with age, suggesting a progressive decline in functioning over time relative to children with ADHD [65]. Children with PAE were also found to have more difficulties with conditions associated with over-arousal, whereas children with ADHD and no history of PAE demonstrated deficits in conditions of underarousal [101].…”
Section: Child Psychiatry Hum Devmentioning
confidence: 96%
“…Notably, adaptive behavior deficits cannot be fully explained by decrements in IQ or a history of environmental disruption [64]. Children with PAE have been found to show delayed adaptive function even compared to those with Attention Deficit, Hyperactivity Disorder (ADHD), with socialization and communication impairments increasing with age [65]. Compared to healthy controls, young children with PAE need more intensive levels of adaptive support from parents and teachers [66].…”
Section: Impairments In Adaptive Functioningmentioning
confidence: 99%
“…These include hyperactivity (e.g., Aronson et al 1997;Mick et al 2002;Crocker et al 2009), conduct problems and oppositional behavior (e.g., Fryer et al 2007; Ryan and Ferguson 2006;Steinhausen et al 2003;Weinberg 1997), depression (e.g., Fryer et al 2007), and anxiety (Steinhausen et al 2003). It is, therefore, not surprising that poor academic achievement is also common among children with PAE (Fryer et al 2007).…”
mentioning
confidence: 93%
“…Attention deficit hyperactivity disorder (ADHD) is present in many cases of FASD and was suggested as a core deficit in FASD [100;101]. However, the impairments in adaptive function or cognitive ability in individuals with ADHD and FASD appeared distinct in certain respects [102][103][104].…”
Section: Altered Brain Network Recruitment and Activation In Task Permentioning
confidence: 99%